2017
DOI: 10.1038/srep43137
|View full text |Cite
|
Sign up to set email alerts
|

Dezocine exhibits antihypersensitivity activities in neuropathy through spinal μ-opioid receptor activation and norepinephrine reuptake inhibition

Abstract: Dezocine is the number one opioid painkiller prescribed and sold in China, occupying 44% of the nation’s opioid analgesics market today and far ahead of the gold-standard morphine. We discovered the mechanisms underlying dezocine antihypersensitivity activity and assessed their implications to antihypersensitivity tolerance. Dezocine, given subcutaneously in spinal nerve-ligated neuropathic rats, time- and dose-dependently produced mechanical antiallodynia and thermal antihyperalgesia, significantly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Dezocine is first discovered by Pfizer for the treatment of perioperative pain [26]. Later reports demonstrate that dezocine exhibits anti-nociception effect in a rat neuropathic pain model [8], as well as antihypersensitivity in neuropathy by activating μ-opioid receptor in the spinal cord [27].…”
Section: Discussionmentioning
confidence: 99%
“…Dezocine is first discovered by Pfizer for the treatment of perioperative pain [26]. Later reports demonstrate that dezocine exhibits anti-nociception effect in a rat neuropathic pain model [8], as well as antihypersensitivity in neuropathy by activating μ-opioid receptor in the spinal cord [27].…”
Section: Discussionmentioning
confidence: 99%
“…Once known as a mu opioid receptor antagonist and kappa opioid receptor agonist, dezocine has recently been recognized as a weak mu opioid receptor agonist and kappa opioid receptor antagonist, with an inhibitory effect on the re-uptake of noradrenalin and serotonin [ 10 , 11 , 17 , 18 ]. Several reports have suggested that dezocine possesses a potent analgesic effect, and thus, it has been used in perioperative pain management [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hindpaw withdrawal threshold to mechanical stimuli was measured using a 2290CE electrical von Frey hair (IITC Life Science Inc., CA, USA) according to the previous study [46]. Neuropathic rats were acclimatized to the Plexiglas box on a metal grid for at least 30 minutes.…”
Section: Mechanical Allodynia Assessmentmentioning
confidence: 99%